Impact of time interval and dose rate on cell survival following low-dose fractionated exposures. (8th June 2017) - Terashima, Shingo; Hosokawa, Yoichiro; Tsuruga, Eichi; Mariya, Yasushi; Nakamura, Toshiya
Abstract: Enhanced cell lethality, also known as hyper-radiosensitivity, has been reported at low doses of radiation (≤0.5 Gy) in various cell lines, and is expected to be an effective cancer therapy. We conducted this study to examine the impact of time interval and dose rate of low-dose fractionated exposures with a short time interval. We evaluated the cell-survival rates of V79 and A549 cells using clonogenic assays. We performed fractionated exposures in unit doses of 0.25, 0.5, 1.0 and 2.0 Gy. We exposed the cells to 2 Gy of X-rays (i) at dose-rates of 1.0, 1.5 and 2.0 Gy/min at 1-min intervals and (ii) at a dose-rate of 2.0 Gy/min at 10-s, 1-min and 3-min intervals by fractionated exposures. Apoptosis and cell cycle analyses were also evaluated in the fractionated exposures (unit dose 0.25 Gy) and compared with single exposures by using flow cytometry. Both cell-type survival rates with fractionated exposures (unit dose 0.25 Gy) with short time intervals were markedly lower than those for single exposures delivering the same dose. When the dose rates were lower, the cytotoxic effect decreased compared with exposure to a dose-rate of 2.0 Gy/min. On the other hand, levels of apoptosis and cell cycle distribution were not significantly different between low-dose fractionated exposures and single exposures in either cell line. These results indicate that a stronger cytotoxic effect was induced with low-dose fractionated exposures with a short time interval for a given dose due to the hyper-radiosensitivity phenomenon, suggesting that dose rates are important for effective low-dose fractionated exposures.